Development of a certification methodology for “green” roofs - Lisienkova Liubov; Rekus Irina; Rodionova Svetlana (BIO Web of Conferences)
This study examines design solutions in construction aimed at creating ecosystems within urban environments. The focus of the study are”green” roofs as a part of “green” building practices (next – green). The problem lies in the lack of a certification methodology for green roofs. The challenge of designing and constructing green building elements is associated with the absence of a certification system for such structures. The aim of this work is to develop a certification methodology for green roofs, which will facilitate the active implementation of such structures in construction and positively impact the ecology of Russian cities. The study covers the analysis of green roofs design and construction, developmentof the stages for green roofs installation, formulating the nomenclature basis of quality indicators for roofing materials, shaping the requirements of normative-technical documentation for conformity assessment, and development of certification schemes for green roofs. The practical result of this work is the development of a certification methodology for green roofs. The methodology can standardize the procedure for conformity assessment to normative values and ensure the objectivity of quality control for green roofs during the design and construction process.